CHARGING HIGH SCHOOL REPORT CARDS ONLINE APPLICATION MENGGUNAKKAN MACROMEDIA DREAMWEAVER 8.0, PHP AND MYSQL - Linda Oktaviani; Irfan, SKom, MMSI Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2010)
Website on the Internet is an effective means to convey information a product or acompany with fast, accurate, and can be accounted for authenticity.Filling the list of values rapport via Internet network capable of providingconvenience and could increase the efficiency in terms of filling in report cards forteachers SMU.Untuk implementations use server side scripting language PHP(Personal Home Page) for information on the site can be accessed through the internetnetwork and therefore take advantage of MySQL software contents of the site moreattractive and dynamic.This website is expected to homeroom teachers in particular can be easily andefficiently in a process of filling their students' report cards list of values.